Did State Pre-Kindergarten Programs Affect the Head Start Enrollment of Children with Disabilities? A Quasi-Experimental Analysis. (January 2023) - Zhang, Qing; Jenkins, Jade Marcus
Little is known about how the expansion of state pre-kindergarten (pre-k) programs affects low-income children with disabilities in Head Start. Using almost 30 years of administrative data of all Head Start programs and a differences-in-differences design, this study tests the possibility that, as state pre-k differentially draws relatively more advantaged children from the pool of eligible 4-year-olds, Head Start taps into their relative programmatic strengths and serves more children with disabilities. We found that, overall, the introduction of state pre-k was associated with a 1 percentage point (7%) decrease in Head Start enrollment of children with disabilities. However, Head Start programs located in school systems did experience an increase in their enrollment of children with disabilities identified before Head Start enrollment. We also found that the decrease was primarily driven by children with speech impairment, suggesting that state pre-k might affect the Head Start enrollment of children with disabilities through "cream-skimming" because services for these children are relatively more common and less expensive. Implications for future research and practice are discussed.